NYX VISCA CHENSIS SP. NOV. PARA CHILE (LEPIDOPTERA: CHOREUTIDAE) (Acta Entomológica Chilena, 2022)
Nyx viscachensis sp. nov. of Choreutidae from central Chile is described. Diagnostic characters and hostplant are recognised. Figures of adult male and female, genitalia and a key for Nyx species are provided.
Keywords: Choreutidae, Nyx, taxonomy, Chile